Simulation of wind fields over Point Arguello, California, by wind-tunnel flow over a topographic model - Cermak, J. E. (Jack E.), author; Peterka, J. A. (Jon A.), author; Fluid Dynamics and Diffusion Laboratory, College of Engineering, Colorado State University, publisher (Colorado State University. Libraries, 1966)
Stably stratified flow over a 1:12,000 scale model of the U.S. Naval Missile Facility at Point Arguello, California was studied in the Army Meteorological wind tunnel of the Fluid Dynamics and Diffusion Laboratory at Colorado State University. Mean temperature, mean velocity and mean concentration distributions obtained for the laboratory flow were compared with available field data collected at the site. These comparisons revealed that the geometrical, dynamic and thermal similarity were sufficiently achieved to give similar mean flow patterns, temperature distributions and concentration decay rates for diffusing tracers. The data revealed that a laminar laboratory flow may be used to simulate a turbulent field flow under conditions of stable thermal stratification and complex terrain. In such flow conditions, diffusion is dominated by convective dispersion.
CER65JEC-JAP64.
November 1966.
Prepared under U.S. Navy Contract N123(61756)34361A(PMR), U.S. Navy Purchasing Office, Los Angeles, California.
Keywords: Winds -- California -- Point Arguello -- Charts, diagrams, etc.; Wind tunnels -- Flow visualization